Relational capital for shared vision in innovation ecosystems - Martha G. Russell; Jukka Huhtamäki; Kaisa Still; Neil Rubens; Rahul C. Basole (Triple Helix, 2015)
This paper provides an evidence-based approach to understanding the relationship infrastructure of spatially defined innovation ecosystems in three metropolitan areas. With the Triple Helix framework, the ecosystem perspective, and shared vision for transformation initiatives, we explore relationships as structure in the metropolitan areas of Austin, TX; Minneapolis, MN; and Paris, France. Network metrics are interpreted as indicators of relational capital; and network visualizations reveal distinct patterns of relational space that structure business ecosystems at the enterprise, growth, and startup levels in each geographic area. We illustrate that network metrics, relationship indicators, and their visualization can be valuable resources for quantitatively and qualitatively investigating and analyzing the complexities of engagement, agility, vitality, linking, and embeddedness in innovation ecosystems. We suggest that data-driven indicators of relational capital may be used for network orchestration, evidence-based policy, and the development of shared vision in spatially defined business ecosystems.
Keywords: 330; Innovation; Networks; Business; Ecosystem; Metropolitan; Relationships; Visualization